Adequately identifying low-risk chest pain in emergency primary care: evaluating the performance of preHEAR(T) based on two European cohorts - Sigrun Halvorsen; Ralf E Harskamp; Dan Atar; Tonje R Johannessen; Odd Martin Vallersnes; Amy Manten; Indra M B Melessen (Open Heart, 2025)
Background Differentiating cardiac from non-cardiac acute chest pain poses a diagnostic challenge, especially in primary care. The History, ECG, Age, Risk factors and Troponin level (HEART) score aid in risk stratification in hospitals, while the prehospital HEART (preHEART) score was refined for paramedics’ use. However, its accuracy in emergency primary care has not been studied. This study evaluates the preHEAR(T) score, with and without high-sensitivity cardiac troponin (hs-cTn), as a tool to rule out acute myocardial infarction (MI) in emergency primary care.Methods Retrospective data from two European cohorts were analysed, namely the One-hoUr Troponin in a low-prevalence population of Acute Coronary Syndrome (OUT-ACS) study (1711 patients) at a Norwegian emergency primary care centre (2016–2018) and the TRiage of Acute Chest pain Evaluated in urgent primary care (TRACE) study (664 patients) at a Dutch emergency primary care centre (2017). The preHEAR (without hs-cTn) score was evaluated in both cohorts. The preHEART score was assessed in OUT-ACS only, as the TRACE study did not measure troponins. The threshold of ≤3 points has previously been determined as low risk for acute MI (AMI) and optimal for rule-out purposes. The primary outcome was diagnostic performance for ruling out MI, and the secondary outcome was the composite of 90-day AMI or all-cause death.Results In OUT-ACS, 3.6% of patients had an AMI (median age 56 years (45–68); 47.7% female), and 3% in TRACE (median age 48 years (32–67); 56.9% female). PreHEAR identified 49.3% (OUT-ACS) and 82.7% (TRACE) as low risk, while preHEART identified 33.6% (OUT-ACS) as low risk. Sensitivity/specificity for AMI were 63.9% (95% CI 50.6 to 75.8)/49.8% (95% CI 47.3 to 52.7) (OUT-ACS) and 65% (95% CI 40.8 to 84.6)/84.2% (95% CI 81.1 to 86.9) (TRACE) for preHEAR and 93.4% (95% CI 84.1 to 98.2)/34.6% (95% CI 32.2 to 37) for preHEART. For the secondary outcome, similar diagnostic performance metrics were found. There were four missed AMI cases in the low-risk preHEART group, who were all female.Conclusion Neither the preHEAR nor preHEART scores provide sufficient rule out safety in emergency primary care and may particularly underestimate AMI risk in females.Trial registration number OUT-ACS: clinicaltrials.gov NCT02983123. TRACE: Netherlands Trial Registry (NL-OMON20102); https://onderzoekmetmensen.nl/nl/trial/20102.